Split application of liquid urea as a tool to nitrogen loss minimization and NUE improvement of corn - A review - Md Motasim, Ahmmed; Samsuri, Abd Wahid; Abdul-Sukor, Arina Shairah; Mohd. Amin, Adibah (Instituto de Investigaciones Agropecuarias, 2022)
Nitrogen loss minimization is the main challenge to sustainable crop production and reducing environmental and economic losses. There is a new approach to urea application in liquid form (LU) so that the NH4 + can be evenly distributed throughout the soil profile, soil particles adsorb it and reduce the local substrate concentration inhibiting further transformation. Liquid urea has been hydrolyzed even prior to soil a pplication, whereas the urea in granulated urea (GU) must be hydrolyzed after application before it can be transformed to NH4 +. Increased urea application frequency with lower doses can lower the NH4 + concentration in soil compared to a single application. These mechanisms reduce the N loss potential and increase the N crop uptake potential of applied N by conforming to the proper synchronization between N availability and crop N demand as well as reduce N loss potential as NH3 volatilization, NO3 - leaching and N2O emission. The inconsistent results and clarifications from various studies highlight the importance and benefits of relating the effect of LU application on N loss minimization, N availability and corn (Zea mays L.) yield. This review summarizes the potential ways of N losses and their management and provides the scientific reference to achieve sustainable corn yield and reduce N losses.